Upaya Orang Tua dalam Mengatasi Kecanduan Gedget pada Anak Usia Dini di Kelurahan Napal Kabupaten Seluma - Nur Afifa, Ira (Yayasan Darussalam Bengkulu, 2022)
This study aims to determine the efforts of parents in dealing with children who are addicted to gadgets and to find out the obstacles of parents in dealing with children who are addicted to gadgets. In this study, there is a formulation of the problem, namely how parents' efforts in dealing with children who are addicted to gadgets, what are the obstacles of parents in dealing with children who are addicted to gadgets? The subjects in this study were parents in Napal Village, Seluma Regency. The method used in this research is qualitative method. The data analysis technique uses Interactive model data analysis. Data collection techniques in this study used interviews, observation and documentation. The results of this study found that Parents' Efforts in Overcoming Gadget Addiction in Children are (a) mentoring the use of gadgets in children, (b) limit the use of gadgets in children, (c) choose according to the age of the child, (d) set a good example and the obstacles faced by parents in dealing with children who are addicted to gadgets are (a) covering some housewives in terms of daily activities, such as doing household chores such as cooking, washing and cleaning the house, (b) children's obstacles are difficulty eating, forgetting to eat, difficulty sleeping, children will frown and cry if they are not lent or allowed to use gadgets, besides that children will fuss when the mother is doing housework (c) the obstacles experienced by some working parents are limited time to interact with children because they are rarely at home.